Strategy for the Development of Salak Fruit Business - Unifah, Unifah (Efficient: Indonesian Journal of Development Economics, 2019)
Agricultural value added can be increased through with off farm agribusiness, one of wich is horticultural commodities such as zalacca fruit to increase the price of the commodity. There are must be post harvest handling such as processing of zalacca juice by Women Farmer Group (KWT) Mekarsari in Kupangan Village of Wonosobo Regency. Some obstacles experienced by wire Mekarsari doing zalacca juice processing business include the skill of human resources that are have low skill, quality products are not durable and product marketing is still low. The purpose of this research is to establish priorities for the development strategy zalacca juice processing business in Kupangan Village Wonosobo Regency. This research uses Analytical Network Process (ANP) method with use Super Decision software. ANP can accommodate the interrelationship between criteria or between alternatives where there is a linkage in one element (inner dependence) and the interrelationship between different elements (outer dependence). ANP analysis results show there are three alternative business development processing of the zalacca juice of KWT Mekarsari produces aspects of product quality as the top priority and the right strategy to improve the quality of long lasting zalacca juice products. Recommendation strategy to improve product quality is the highest priority strategy, is 0.4764. Nilai tambah pertanian dapat ditingkatkan melalui agribisnis di luar pertanian, salah satunya adalah komoditas hortikultura seperti buah salak untuk meningkatkan harga komoditas tersebut. Harus ada penanganan pasca panen seperti pengolahan jus zalacca oleh Kelompok Tani Wanita (KWT) Mekarsari di Desa Kupangan, Kabupaten Wonosobo. Beberapa kendala yang dialami oleh kawat Mekarsari dalam melakukan bisnis pengolahan jus zakat antara lain keterampilan sumber daya manusia yang memiliki keterampilan rendah, produk berkualitas tidak tahan lama dan pemasaran produk masih rendah. Tujuan dari penelitian ini adalah menetapkan prioritas strategi pengembangan bisnis pengolahan jus zakat di Desa Kupangan Kabupaten Wonosobo. Penelitian ini menggunakan metode Analytical Network Process (ANP) dengan menggunakan perangkat lunak Super Decision. ANP dapat mengakomodasi keterkaitan antara kriteria atau antara alternatif di mana ada keterkaitan dalam satu elemen (ketergantungan dalam) dan keterkaitan antara elemen yang berbeda (ketergantungan luar). Hasil analisis ANP menunjukkan ada tiga alternatif pengembangan bisnis pengolahan jus zalak dari KWT Mekarsari menghasilkan aspek kualitas produk sebagai prioritas utama dan strategi yang tepat untuk meningkatkan kualitas produk jus zalacca yang tahan lama. Strategi rekomendasi untuk meningkatkan kualitas produk adalah strategi prioritas tertinggi, yaitu 0,4764.